Improving Speaking Skill by Using Group Work Method - Merla Madjid (Universitas Gadjah Mada, 2019)
There are four skills in English and one of the skills that students think is very difficult is speaking. Speaking is the skill that needs more practice and exercise, otherwise speaking fluency cannot be improved. Teacher needs to use different teaching techniques in order to reach all students effectively. The objective of this research is to see whether the method in teaching Speaking English by using the group work technique has a positive effect on the academic achievement of the students at Polytechnic ATIM (ATI Makassar), especially for Agro Industrial Engineering students who studied at the second grade. This research was carried out through class action research where teacher gives some materials, apply the method, then give direct testing such as written test to find out how far students understand about the materials after they discussed in group. It is one of the assessment materials. Others assessments are taken from groups’ activities in class room, groups’ presentation, Individual’s interview test and questionnaire. This technique plays a positive role in improving the academic achievement in speaking. The technique can also improve students’ motivation in learning English; develop their Self-confidence and cooperation among students. The finding from questionnaire proves that this method can also be used to improve students’ mastery of grammar in use and motivate students in learning grammar. The method promotes learner autonomy by allowing students to make their own decision in the group without being told what to do by the teacher.